Deadly combinations: how leadership contexts undermine the activation and enactment of followers' high core self-evaluations in performance. Issue 3 (4th May 2018) - Soane, Emma; Booth, Jonathan E.; Alfes, Kerstin; Shantz, Amanda; Bailey, Catherine
ABSTRACT: Employees with high core self-evaluations (CSE) generally perform well in their jobs. The enactment of CSE in performance occurs within contexts, and leadership is one form of context that influences the activation and expression of CSE. Drawing on theories of CSE and leader–member exchange (LMX), we characterized the leadership context as the interaction between leader CSE and LMX quality. Examination of 173 followers and their 31 leaders in a manufacturing organization showed a positive association between follower CSE and performance when the context comprised high leader CSE and high LMX. Conversely, leadership contexts comprising high leader CSE and low LMX, or low leader CSE and high LMX, resulted in a negative relationship between follower CSE and performance. We also show that low CSE followers have relatively high performance under some circumstances. Thus, we contribute to understanding how some leadership contexts undermine high CSE followers' performance and promote low CSE followers' performance.